Analysis of emotional maturity, family harmony and aggressive behavior in students - Anisah Tanjung; Marjohan Marjohan; Yeni Karneli (Counseling and Humanities Review, 2021)
This study aims to see how (1) the level of emotional maturity, (2) the level of family harmony, and (3) the level of student aggressive behavior. This type of research is descriptive quantitative research with the object of research being SMA. The sample of this study consisted of 30 high school students. The instrument used in this study was the Likert scale model, and the instrument used had been tested for validity and reliability. The results showed that: (1) overall emotional maturity was in the high category with a percentage of 80%, (2) overall family harmony was in the good category with a percentage of 57%, and (3) overall aggressive behavior was at the high category with a percentage of 57%.